2022
DOI: 10.1177/10668969221117978
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Neurofibroma/Schwannoma of the Oral Cavity: A Rare Case Report and Literature Review

Abstract: Hybrid peripheral nerve sheath tumors show combined features of more than one type of conventional benign peripheral nerve sheath tumors. There are few cases reported of hybrid peripheral nerve sheath tumors in the head and neck region. A 68-year-old female patient was referred for evaluation of an oral swelling lasting five years. Intraoral examination revealed a small mobile nodule located in the lower vestibule. The patient underwent excisional biopsy and microscopic evaluation showed typical features of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…Recognition of hybrid neural lesions is important, as some may be associated with syndromes, especially neurofibromatosis types 1 and 2 and the patient may have multiple lesions. 2 In our case, the clinical investigation did not reveal other findings that could indicate a syndromic condition of the patient.…”
contrasting
confidence: 54%
See 2 more Smart Citations
“…Recognition of hybrid neural lesions is important, as some may be associated with syndromes, especially neurofibromatosis types 1 and 2 and the patient may have multiple lesions. 2 In our case, the clinical investigation did not reveal other findings that could indicate a syndromic condition of the patient.…”
contrasting
confidence: 54%
“…1 About 17 patients with this type of tumor located in the head and neck region have been described in the literature, and most was neurofibroma-schwannoma type. 2 Kazakov et al 3 (2005) reported two hybrid neurofibromaperineurioma tumors in the skin of the mammary and scapular region, whose diagnosis was established because they observed a biphasic pattern with two components, which resembled or were morphologically and immunohistochemically identical to a neurofibroma or perineurioma. 3 Despite the fact that some neurofibromas have a subpopulation of perineural cells, 4 in the present case, we saw clearly two distinct areas that morphologically resembled a perineurioma and a neurofibroma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In those cases, MRI imaging should always be performed to avoid any unnecessary treatment complications [29][30][31][32]. In the literature, only one hybrid ONT tumour type, namely, a neurofibroma-schwannoma tumour, was reported by Leite et al [33]. Surgical removal is the treatment of choice for each patient; however, multiple SCs or even solitary SCs can be associated with some syndromic disorders; therefore, a detailed patient anamnesis is important [25][26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, only one hybrid ONT tumour type, namely, a neurofibroma-schwannoma tumour, was reported by Leite et al [33]. Surgical removal is the treatment of choice for each patient; however, multiple SCs or even solitary SCs can be associated with some syndromic disorders; therefore, a detailed patient anamnesis is important [25][26][27][28][29][30][31][32][33]. Each site of the oral cavity might be associated with a schwannoma.…”
Section: Discussionmentioning
confidence: 99%